Lichen ranges, animal densities and production in Finnish reindeer management - T. Helle; S.-S. Kilpelä; P. Aikio (Rangifer, 1990)
In the 1970s, mean lichen biomass ranged by the earmark districts (comprising of 2-9 adjacent herding associations) between 54 kg and 380 kg DM per ha correlating negatively with animal density per lichen ranges (range 1.5 - 14.3 ind. per km2). Biomasses were far below economic carrying capacity of lichen ranges (900 kg DM per ha). The condition of lichen ranges was poorest in the southern half of the area where alternative food to reindeer lichens (Deschampsia flexuosa, arboreal lichens and supplementary feeding) was available. In 1980-86, recruitment (calves per 100 females) was 33% higher than in the 1970's, on an average (65 vs. 49), despite a 90% increase in animal numbers between 1970 and 1986; recruitment has not been dependent on the condition of lichen ranges. The increase in production has been some higher than expected on the basis of animal numbers. The reasons for the increasing trends in animal numbers, recruitment and production remains some unclear, but they may include favorable winter conditions, supplementary feeding, medical treatment against parasites and proper harvesting policy.